Skeletal muscle interleukin‐6 regulates metabolic factors in iWAT during HFD and exercise training. (22nd June 2015) - Knudsen, Jakob G.; Bertholdt, Lærke; Joensen, Ella; Lassen, Signe B.; Hidalgo, Juan; Pilegaard, Henriette
Abstract : Objective: To investigate the role of skeletal muscle (SkM) interleukin (IL)‐6 in the regulation of adipose tissue metabolism. Methods: Muscle‐specific IL‐6 knockout (IL‐6 MKO) and IL‐6 loxP/loxP (Floxed) mice were subjected to standard rodent diet (Chow), high‐fat diet (HFD), or HFD in combination with exercise training (HFD ExTr) for 16 weeks. Results: Total fat mass increased ( P  < 0.05) in both genotypes with HFD. However, HFD IL‐6 MKO mice had lower ( P  < 0.05) inguinal adipose tissue (iWAT) mass than HFD Floxed mice. Accordingly, iWAT glucose transporter 4 (GLUT4) protein content, 5′AMP activated protein kinase (AMPK) Thr172 phosphorylation, and fatty acid synthase (FAS) mRNA content were lower ( P  < 0.05) in IL‐6 MKO than Floxed mice on Chow. In addition, iWAT AMPK Thr172 and hormone‐sensitive lipase (HSL) Ser565 phosphorylation as well as perilipin protein content was higher ( P  < 0.05) in HFD IL‐6 MKO than HFD Floxed mice, and pyruvate dehydrogenase E1α (PDH‐E1α) protein content was higher ( P  < 0.05) in HFD ExTr IL‐6 MKO than HFD ExTr Floxed mice. Conclusions: These findings indicate that SkM IL‐6 affects iWAT mass through regulation of glucose uptake capacity as well as lipogenic and lipolytic factors.